Perbandingan Pajak dan Retribusi Dengan Zakat Dalam Perspektif Maqashid Syariah (Kajian Perbandingan Pajak dan Retribusi Dengan Zakat Di Indonesia) - Uly Mabruroh Halida (TAFAQQUH, 2020)
This study aims to determine the difference between tax and zakat in the perspective of maqashid shariah and know the study of potential taxes and levies with zakat in solving development problems. Conducted with descriptive quantitative approach with Documentation and Library Review method. The result of the research is the difference between zakat and tax in the perception of maqashid syariah are: 1) Zakat is a manifestation of the obedience of the Ummah against the commands of Allah SWT and Rasulullah SAW while the tax is the obedience of a citizen to the leader (ruler). 2) Zakat has been determined in the Koran and al-Hadith, while the tax is formed by the law of the state. 3) Zakat is only issued by the Muslims while taxes are issued by every citizen regardless of religion and belief. 4) Zakat applies to every Muslim who has attained nishab regardless of where he / she lives, while taxes apply only within the territorial borders of a country. 5) Zakat is a worship that must be preceded by intention while the tax does not use the intention. Study the potential of taxes and levies with zakat in solving development problems. 1) That which affects poverty are taxes, DAU and retribution. 2) the effect on unemployment are taxes, DAU and retribution 3) While affecting the Human Development Index (IPM) is the tax and DAU.